The Relationship Of Mother's Behavior About Neck Cancer In The Papsmear Examination At The Pancur Batu Health Center Year 2020 - Siti Meilan Simbolon; Ristika Julianty Singarimbun (Sean Institute, 2021)
Cervical cancer has the highest incidence rate in developing countries and developed countries rank second after breast cancer. WHO notes that in the world every year there are 5.25 million people with cancer. Most sufferers come at an advanced stage to check themselves. Based on data from the Pancur Batu Health Center, every year the number of cervical cancer sufferers in 2019-2020 has increased from 96 people to 126 people. For this reason, researchers feel the need to conduct research on